Fungsi Sastra Lisan Banjar Tatangar - Hestiyana Hestiyana (Kantor Bahasa Provinsi Maluku Utara, 2017)
This study addresses the issue of oral literature Banjar tatangar function with the aim to describe the function of oral literature Banjar tatangar. The theory used is the theory of William R. Bascom. The method used in this research is descriptive qualitative method. Techniques of collecting data are the documentation, recordings, and interviews. Furthermore, in the technique of data analysis used descriptive analysis, by analyzing one by one tatangar accordance with its function. Sources of data used in this study: (1) primary data, namely informants in the field as many as three people were categorized as oral literature Banjar tatangar speakers residing in Hulu Sungai Selatan, Hulu Sungai Tengah and Hulu Sungai Utara; and (2) secondary data, ie data obtained from the complement existing research related to the study of oral literature Banjar tatangar. Based on the analysis found four functions Banjar tatangar oral literature, namely: (1) tatangar function as a form of entertainment; (2) functions as an instrument of ratification tatangar institutions and cultural institutions; (3) tatangar function as an educational tool children; and (4) tatangar function as a means of coercion and supervisors so that society's norms will be respected member of the collective